Late-Antique Studies in Memory of Alan Cameron - Harris, William V.,; Chen, Anne Hunnell, (Columbia Studies in the Classical Tradition ;, 2021)
The classicist and historian Alan Cameron (1938-2017) was, among other achievements, one of the scholars who most contributed to the refoundation of late-antique studies. In this tribute W. V. Harris and Anne Hunnell Chen have brought together fourteen contributions that cover a broad range of historical, literary, and art-historical topics, running from the first century AD to the ninth. Some contributions concern Cameron's own favourite themes (the Greek Anthology, the Historia Augusta , circus factions, the transmission of texts), while others seek to assess his work and its impact. Other papers branch out from his concerns to discuss slavery, simony, and hospitals. Fourth- and fifth-century writers are often to the fore and the volume includes a new text by the poet Dioscoros of Aphrodite.